Intradural lipoma at the foramen magnum presenting with classical Chiari symptoms: A case report. (August 2015) - Marsden, Nick; Stimpson, Amy; Al-Baqer, Hayder; Leach, Paul
Abstract Intradural lipomas are rare lesions, usually associated with spinal dysraphism, affecting the spinal cord. Intracranial lipomas make up less than 1% of intracranial tumours; only 13 cases of these lesions being located at the craniocervical junction are reported in the literature. These lesions tend to present with neurological deficits such as quadraparesis and incontinence. We present the first case of a successfully treated intradural lipoma at the foramen magnum in a 15-year-old girl who presented with classical Chiari symptoms and no neurological deficits.